2015
DOI: 10.1007/s00405-015-3852-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vocal outcome following two different procedures for immediate RLN reconstruction

Abstract: The objective of this study was to compare time-dependent improvements in phonatory function and stroboscopic findings following two different procedures for immediate reconstruction of the recurrent laryngeal nerve (RLN) during neck tumor extirpation. Seventeen patients with neck tumors, consisting of advanced thyroid cancer (n = 15), metastatic neck lymph nodes from other malignant lesions (n = 2), underwent resection of the primary lesion and involved RLN. Immediate RLN reconstruction by either: (1) ansa ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Primary intraoperative RLN reinnervation is theoretically an ideal approach for improving voice due to UVFP. Intraoperative RLN reinnervation, in which neurorrhaphy is performed between the distal RLN and intact proximal RLN (primary reanastomosis or greater auricular nerve [GAN] free grafts) or other intact nerves, including the ansa cervicalis (ansa-RLN) and hypoglossal nerve (hypoglossal-RLN) during the surgical procedure, may prevent progressive loss of thyroarytenoid muscle tension and bulk [ 139 ]. By using this procedure at the time of surgery, subsequent medialization procedures may be avoided.…”
Section: Guidelines For the Management Of Uvfpmentioning
confidence: 99%
“…Primary intraoperative RLN reinnervation is theoretically an ideal approach for improving voice due to UVFP. Intraoperative RLN reinnervation, in which neurorrhaphy is performed between the distal RLN and intact proximal RLN (primary reanastomosis or greater auricular nerve [GAN] free grafts) or other intact nerves, including the ansa cervicalis (ansa-RLN) and hypoglossal nerve (hypoglossal-RLN) during the surgical procedure, may prevent progressive loss of thyroarytenoid muscle tension and bulk [ 139 ]. By using this procedure at the time of surgery, subsequent medialization procedures may be avoided.…”
Section: Guidelines For the Management Of Uvfpmentioning
confidence: 99%
“…However, other nerves are available when the ACN is hard to obtain or unsuitable. There were no significant differences between the great auricular nerve (GAN) reconstruction with the RLN and ACN to RLN anastomosis in a previous study (29). A follow-up study about the of 237 cases with ACN reinnervation showed that phonatory function could be normal after nerve-grafting (23).…”
Section: Neuroanastomosis and Reinnervationmentioning
confidence: 85%
“…Table I summarizes the outcomes of the characteristics and outcomes of papers published reporting IIORRLN (Table I). Kumai et al, specifically found no differences on the type of anastomoses when comparing FNG and ARA 49 . And furthermore Yoshioka et al, found no differences in outcomes between all four main types of reconstruction DA, FN, ARA, and VRA 28 .…”
Section: Outcomes Of Iiorrlnmentioning
confidence: 97%